Acute Small Gut Obstruction as an Atypical Presentation of Acute Appendicitis without Rupture or Perforation of the Appendix - Moniruddin, ABM; Chowdhury, Salma; Hasan, Tanvirul; Mahmudul Hasan, Kazi Muhammad; RounakJahan, -; Hossain, Kabir Ashfaque (Journal of Bangladesh College of Physicians and Surgeons, 2021)
Acute appendicitis is a very common surgical emergency. It has got diverse presentations and various complications. Here, we report case history of a young male patient with a 2- year history of recurrent abdominal pain, who presented to our center with a 4-day history of increasing abdominal pain, constipation and vomiting. Clinical and radiological evaluation revealed it as a case of acute intestinal obstruction preoperatively. Per-operative findings suggested acute appendicitis without perforation, small gut obstruction by adhesions, appendicular lump or internal herniation. Appendicectomy was done along with other necessary procedures. His post-operative period was uneventful. This case is reported here to highlight that acute appendicitis may present with atypical features like acute small gut obstruction. J Bangladesh Coll Phys Surg 2021; 39: 261-265